Hybrid extracellular vesicles for drug delivery. (1st April 2023) - Ducrot, Coline; Loiseau, Stanislas; Wong, Christophe; Madec, Elise; Volatron, Jeanne; Piffoux, Max
Abstract: Extracellular vesicles (EVs) are expected to serve as interesting drug delivery vectors as they may offer unique and new properties for drug delivery. Their natural origin, protein and nucleic acid composition, and intrinsic pleiotropic therapeutic effects could enable new possibilities in the field of drug delivery. Here, we aimed to review the methods used to produce Hybrid EVs, a recently emerged type of EV-based vector made from both EVs and synthetic vectors to exploit their respective properties. Hybrid EV/synthetic objects can be obtained by incubation, electrostatic interactions, polyethylene glycol (PEG)-mediated fusion, co-extrusion, freeze-thawing, or simple EV surface modification, leading to different types of objects. We also opted to review the properties of these vectors, and specifically compared them with those of other drug delivery vectors. It has to be noticed that only a limited number of study report loading metrics that allow cross article comparison. Based on this critical analysis, we attempted to draw the pith and marrow from these relatively difficult-to-compare studies and integrate them into the more general context of opportunities in drug delivery and drug development, with a particular focus on oncology. Highlights: Hybrid extracellular vesicles are vectors made of an extracellular vesicle (EV) merged with a synthetic vector They may benefit of the EV interesting pharmacokinetic properties, endosomal escape and/or targeting Hybrids benefit from the versatility and drug loading of synthetic vectors Hybrid production methods lead to highly variable drug loading efficiencies We discuss the interest of these vectors in the broader context of drug delivery in oncology